Conduct disorder in childhood: A case study (Research, Society and Development, 2023)
Conduct disorder (CD) is one of the most common psychiatric diagnoses in childhood, characterized by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a disruptive behavior disorder, which leads to antisocial and violent behavior. It is more prevalent in males, affects approximately 3 out of every 100 school-age children and is linked to several risk factors, such as: genetic, sociocultural, psychological and neurobiological. The present study aimed to expand knowledge related to CT in childhood, in addition to understanding the behaviors, diagnostic criteria and therapeutic approaches. To this end, it reported the case of a child diagnosed with HT and carried out a literature review using the descriptors “conduct disorder” and “child behavior”. The results (case description) were organized from an interview with the biological mother of a child diagnosed with CT. The case was described through eight (8) thematic units, making it possible to notice the presence of several typical behaviors of HT, in addition to the difficulty of diagnosis, since, being a mental disorder, it does not have specific physical traits, and can be confused with the lack of education on the part of the parents. Therefore, one can see the importance of listening in the diagnostic process, so that the physician has an adequate understanding of the reported behaviors, avoiding delaying the correct diagnosis and treatment.